Bioinsecticide Bacillus thuringiensis a Comprehensive Review - Osman, G E H; Already, Rasha; Assaeedi, A S A; Organji, S R; El-Ghareeb, Doaa; Abulreesh, H H; Althubiani, A S (Egyptian journal of biological pest control, 2015)
Control of insect pests in agriculture and of insect vectors of important human diseases is mainly achieved using chemical insecticides. However, use of these chemical insecticides has led to several problems, including environmental pollution and increase in human health problems, such as cancer and several immune system disorders. Although microbial insecticides have been proposed as substitutes for chemicals, their use is limited since most microbes show a narrow spectrum of activity. Moreover, they have low environmental persistence and they require precise application practices, since many of these microbes are specific to young insect larval stages. Isolation and characterization of new insecticidal activities is the target of many pest control programs. Bacillus thuringiensis Berliner (Bt) is a gram positive spore forming bacteria. It forms a spore in an adverse condition. Bt produces protein crystals during sporulation. The protein crystals are consisted of two multigenic families, Cry and Cyt. Cry proteins are toxic to different insect orders. They are toxic to Lepidoptera, Coleoptera, Hymenoptera, Diptera and to nematodes.